Variations of pterygium prevalence by age, gender and geographic characteristics in China: A systematic review and meta-analysis. - Peige Song; Xinlei Chang; Manli Wang; Lin An (PLoS ONE, 2017)
Background Pterygium is a common chronic ophthalmic condition, which may result in significant visual morbidity or lead to blindness in extreme cases. The prevalence of pterygium in China has not been reported at the sub-national level. Methods In this study, we conducted a systematic review and meta-analysis to estimate the prevalence of pterygium in China. China National Knowledge Infrastructure (CNKI), Wanfang, Chinese Biomedicine Literature Database (CBM-SinoMed), PubMed, Embase and Medline were searched before September 2016. We performed a multilevel mixed-effect meta-regression based on the included studies, our results showed that age, gender and latitude were significantly associated with pterygium prevalence. Based on the final model, the age and gender-specific prevalence of pterygium in 31 Chinese provinces (except Hongkong, Macau and Taiwan) and the whole country was generated. Results In 2010, the overall prevalence of pterygium in Chinese people aged 15-84 years was 9.84% (95% CI: 6.72-14.14), and the number of pterygium cases in China was 108.65 million (95% CI: 74.23-156.13). Conclusions In conclusion, the prevalence of pterygium in Chinese population in 2010 was estimated at both the national and provincial levels. The higher burden of pterygium across the country calls for efforts to advocate public health education encouraging people to take appropriate protective measures.